Taurodontism part 2: biomechanics, differential diagnosis, clinical implications and management. (2nd March 2019) - Hasan, Muhammad
Abstract : The first article described history, aetiology, molecular signalling mechanism, epidemiology and classification of taurodontism. This final article of the two-part series focuses on the biomechanics and other clinical aspects of taurodontism. In certain disorders, especially during initial stages, the teeth can appear taurodontic and may complicate diagnosis. These conditions, along with their key features, are highlighted in this article, as are several syndromes relevant to taurodontism. In addition, the sections on imaging and clinical considerations discuss diagnostic methods and management of taurodontic teeth, respectively. Taurodontism, especially in severe forms, can be a root canal challenge. Sometimes, multiple taurodontism is seen in association with various syndromes and perhaps may assist in early diagnosis. CPD/Clinical Relevance: Taurodontism has clinical implications in various dental disciplines, such as endodontics, surgery, orthodontics and prosthodontics. However, it is most relevant to endodontists as this deviation exclusively affects the internal anatomy of teeth.